The Tradition of Spatial Writing: The Case of the Palindrome in between Literature and Architecture - Sotirios Varsamis (Footprint)
In this work I define as spatial writing a kind of writing that could be expressed spatially in text and textually in architecture and that includes examples from both text and buildings. In that sense spatial writing is related not only to literary theory but also to architecture, architectural writing or ‘architecture writing’.